Muslim women today : challenges in achieving their full potential in resource management - Panjalingam, Nesamalar (IIUM Press, 2012)
Islam advocates equality among all people regardless of race, gender, or nationality. However, Muslim women face numerous obstacles that stand in the way of their achieving their full potential in resource management. Certain interpretations of religious teachings and Islamic law, especially those to do with property allocation and divorce deny Muslim women what they are rightfully entitled to. Many patriarchal societies tend to have clearly defined roles for males and females. Besides that, many girls are denied access to educational opportunities although education and learning is greatly revered in Islam. All these factors cause Muslim women to doubt themselves and lack self-confidence in what they could achieve. At work, women are often paid lower salaries and have fewer opportunities for career advancement, especially in the fields of management, technology, and science. In leadership positions they have to fight harder for respect. Many Muslim women in countries like Oman, Pakistan, Indonesia, and other Islamic nations face these challenges. This paper discusses these factors with the hope that understanding them could lead to more efficient management and utilization of resources in Muslim countries.